Example Antarctic minke whale calls from Marine soundscape variation reveals insights into baleen whales and their environment: a case study in central New Zealand - Victoria E. Warren (9633167); Craig McPherson (10200117); Giacomo Giorli (10200120); Kimberly T. Goetz (10200123); Craig A. Radford (9944336) (2021)
.wav file containing Antarctic minke whale calls. Data collected by NIWA, New Zealand, at the South Taranaki Bight recording location, 2nd October 2016.